2019
DOI: 10.1053/j.ackd.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, Immunity, and Oxidative Stress in Hypertension—Partners in Crime?

Abstract: Hypertension is considered as the most common risk factor for cardiovascular disease (CVD). Inflammatory processes link hypertension and CVD, and participate in their pathophysiology. In recent years, there has been an increase in research focused on unraveling the role of inflammation and immune activation in development and maintenance of hypertension. Although inflammation is known to be associated with hypertension, whether inflammation is a cause or effect of hypertension remains to be elucidated. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 108 publications
0
44
0
4
Order By: Relevance
“…Some studies have indicated that lipid peroxidation in ferroptosis can promote the inflammation and regulate the level of different inflammatory cytokines [39,51,52], which is consistent with our results. Moreover, the excessive accumulation of ROS also causes oxidative damage and an inflammatory response in lung tissues [53][54][55]. Ferroptosis is mainly induced by the failure of membrane lipid repair, and further leads to the increase of ROS on the membrane lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that lipid peroxidation in ferroptosis can promote the inflammation and regulate the level of different inflammatory cytokines [39,51,52], which is consistent with our results. Moreover, the excessive accumulation of ROS also causes oxidative damage and an inflammatory response in lung tissues [53][54][55]. Ferroptosis is mainly induced by the failure of membrane lipid repair, and further leads to the increase of ROS on the membrane lipids.…”
Section: Discussionmentioning
confidence: 99%
“…141 There is now extensive experimental and clinical evidence indicating that hypertension is associated with inflammation, fibrosis, and activation of immune cells, processes that are driven in large part by oxidative stress. 142 Tissue expression of adhesion molecules (VCAM-1, ICAM-1), production of inflammatory mediators (monocyte chemotactic peptide 1, tumour necrosis factor, interleukin [IL] 1, IL-6, 1L-17), activation of proinflammatory signalling pathways (MAPK, STAT) and transcription factors (NF-kB, AP-1, HIF-1), and circulating levels of inflammatory biomarkers (C-reactive protein, PAI-1, ILs) are increased in hypertension. [143][144][145][146] Although it still remains unclear whether inflammation is a cause or an effect of hypertension, it is clear that the immune system and ROS are important players.…”
Section: Oxidative Stress and Inflammation In Hypertensionmentioning
confidence: 99%
“…Whether inflammation is a cause or effect of hypertension remains unclear. Since this relationship is further confounded by the fact that several factors associated with hypertension, such as obesity or insulin resistance, are also associated with inflammation [10,12]. A role of a cell surface multi-ligand pattern recognition receptor for advanced glycation end products (RAGE) in pathogenesis of hypertension cannot be excluded.…”
Section: Introductionmentioning
confidence: 99%